ANALISIS KARAKTERISTIK KECELAKAAN DAN FAKTOR PENYEBAB KECELKAAN PADA LOKSI BLACKSPOT DI KOTA KAYU AGUNG - Cahaya Eka Putri (Jurusan Teknik Sipil Fakultas Teknik Universitas Sriwijaya, 2014)
Traffic accidents is instances where a motor vehicle collides with another object and cause damage . traffic accidents is a thing to be avoided by all road users , but sometimes the traffic accident took place instantaneously tibakarena poor road infrastructure or due to negligence of road users themselves . There are three types of injuries suffered by the victim that the victim died of accidents , severe injuries , and minor injuries . Previous research analyzing accident-prone locations using the frequency method in analyzing blackspot determined by the lane per kilometer . After processing the data the importance of the factors that influence the occurrence of accidents such as age , gender , occupation , time , and estimated losses suffered by accident victims . Based on the factors of age , 20% of riders are children under the age ( less than 17 years old ) who do not have a driving license as the cause of the accident . While based on the gender factor involved most of the accidents are men who generally drive a motor vehicle with an average of 83.98 %. Private employees with a percentage of 38.1 % with the highest percentage of the type of work involved in the accident. Blackspot is the location where the accident-prone locations on the site of an accident over and over again. Over a period of three years (2010-2012) the total losses caused by traffic accidents in Kayu Agung city is Rp 3,881,650,000 , -Â